The Effect of Profitability and Leverage on Economic Value Added (Eva) in The Coal Mining Sub-Sector for The Period 2021-2023 - Santoso , Wahyu Purbo (Sharia Journal and Education Center Publishing, 2025)
This research aimed to determine and analyze the effect of Profitability and Leverage Ratios on Economic Value Added (EVA) on Financial Performances of Coal Mining Companies Listed on the IDX for the 2021 – 2023 periods. This research used quantitative methods with a descriptive approach. This research used the Panel Data Regression Analysis Method. The result of this researh showed Return On Equity (ROE) partially had a positive and significant effect on Economic Value Added (EVA). Debt to Equity Ratio (DER) partially had no significant negative effect on Economic Value Added (EVA) in Corporate Business Sustainabilty. Return On Equity Ratio (ROE) and Debt to Equity Ratio (DER) simultaneously or together had a positive and significant effect on Economic Value Added (EVA).